2013 46th Hawaii International Conference on System Sciences 2013
DOI: 10.1109/hicss.2013.621
|View full text |Cite
|
Sign up to set email alerts
|

Exit the E-government Ivory Tower: A Training Strategy -- A Case Study from Austria

Abstract: The national Austrian e-government curriculum aims to train government and public administration staff at all organisational levels, so the training plan needs to be developed on the basis of the national egovernment aims and adapted according to the target groups, the contents and teaching modalities. This paper presents the implementation of the egovernment curriculum in Austria that began in 2006 and continues today. Based on a case study approach, the paper looks at the issues important in the implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Business skills [18]; project management, financial management, performance management [5]; change management [11] politicaladministrative e-policy competencies [11]; legal framework, administrative workflows [4]; public policy [5] Even though the mentioned competencies transcend disciplinary boundaries, they predominantly evoke the impression to be assembled multi-disciplinarily. Most of the competencies can be traced back to specific disciplines and are rarely amalgamated in a truly interdisciplinary manner.…”
Section: Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…Business skills [18]; project management, financial management, performance management [5]; change management [11] politicaladministrative e-policy competencies [11]; legal framework, administrative workflows [4]; public policy [5] Even though the mentioned competencies transcend disciplinary boundaries, they predominantly evoke the impression to be assembled multi-disciplinarily. Most of the competencies can be traced back to specific disciplines and are rarely amalgamated in a truly interdisciplinary manner.…”
Section: Categorymentioning
confidence: 99%
“…Exemplarily assigned knowledge, skills, competencies technical Information technology skills [18], IS design competency [11]; information systems [5] sociotechnical e-government impact [11,12]; technology and egovernment adoption; politics of e-government [12] organizational e-government structures [4]; organizational design [11]; process management [4,11] managerial…”
Section: Categorymentioning
confidence: 99%
“…curriculum) of e-government education. Examples of topics covered included identifying the competencies to be incorporated into e-government curriculum (Hunnius & Schuppan, 2013;Schuppan, 2014), examining the implementation of a nation-wide e-government education curriculum (Edelmann et al, 2013), and appraising the alignment between the duties and responsibilities of Government Chief Information Officers vis-à-vis the curriculum of training programs targeting them (Estevez & Janowski, 2013).…”
Section: E-government Educationmentioning
confidence: 99%
“…Some of the oft cited challenges faced by developing countries include inadequate information infrastructure, poor leadership and weak governance, as well as a lack of human and knowledge capital. In fact, studies have pointed to the importance of knowledgeable and skilled public servants and citizens in achieving e-government success (Dawes & Pardo, 2002;Estevez, Cellary, & Davies, 2014;Edelmann, Parycek, & Schossbock, 2013;Humnius & Schippen, 2013). Even though the need for excellent e-government training programs has often suggested to address such knowledge deficiency (Edelmann et al, 2013;Humnius and Schippen, 2013), a scan of the literature revealed a lack of insights on how an effective e-government training program targeting government executives and citizens can be developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation